Crystallization and preliminary crystallographic characterization of GumK, a membrane-associated glucuronosyltransferase from Xanthomonas campestris required for xanthan polysaccharide synthesis - Barreras, Máximo (International Union of Crystallography, 2006)
GumK is a membrane-associated inverting glucuronosyltransferase that is part of the biosynthetic route of xanthan, an industrially important exopolysaccharide produced by Xanthomonas campestris. The enzyme catalyzes the fourth glycosylation step in the pentasaccharide-P-P-polyisoprenyl assembly, an oligosaccharide diphosphate lipid intermediate in xanthan biosynthesis. GumK has marginal homology to other glycosyltransferases (GTs). It belongs to the CAZy family GT 70, for which no structure is currently available, and indirect biochemical evidence suggests that it also belongs to the GT-B structural superfamily. Crystals of recombinant GumK from X. campestris have been grown that diffract to 1.9 Å resolution. Knowledge of the crystal structure of GumK will help in understanding xanthan biosynthesis and its regulation and will also allow a subsequent rational approach to enzyme design and engineering. The multiwavelength anomalous diffraction approach will be used to solve the phase problem.